Successful treatment of Pseudomonas aeruginosa osteomyelitis with antibiotic monotherapy of limited duration. Issue 3 (September 2017) - Laghmouche, Nadir; Compain, Fabrice; Jannot, Anne-Sophie; Guigui, Pierre; Mainardi, Jean-Luc; Lonjon, Guillaume; Bouyer, Benjamin; Fernandez-Gerlinger, Marie-Paule
Summary: Objectives: The aim of this study was to present a 15-year experience and provide a comprehensive analysis of a large cohort of patients with Pseudomonas aeruginosa osteomyelitis. Methods: We reviewed the medical records of patients admitted to a large French university hospital for P. aeruginosa osteomyelitis over a 15-year period. Patient outcome was assessed at follow-up after at least six months. Results: Sixty-seven patients were included, comprising 57% with chronic osteomyelitis. Polymicrobial infection was predominant (63%), and an infected device was involved in 39% patients. The overall treatment success rate was 79.1%. All but one patient were treated with a combination of surgery and antibiotic therapy. The antibiotic treatment had a mean duration of 45 days (range, 21–90 days). Single-antibiotic therapy was preferred in nearly all cases. Treatment failure was reported for 14 (21%) patients and was due to the persistence of P. aeruginosa in four cases. No significant risk factor for treatment failure was identified, especially when treatment strategies were compared. Conclusions: We advocate optimal surgical debridement combined with initial parenteral antibiotics for a maximum of 15 days, followed by an oral fluoroquinolone. Total treatment duration should not exceed six weeks, and antibiotic treatment with two-drug combinations does not seem necessary.